Charge Pickup Reaction Cross Section for Neutron-Rich p-Shell Isotopes at 900A MeV - J.-C. Zhang; B.-H. Sun; I. Tanihata; S. Terashima; F. Wang; R. Kanungo; C. Scheidenberger; F. Ameil; J. Atkinson; Y. Ayyad; S. Bagchi; D. Cortina-Gil; et al. (Physical Review X)
We report charge pickup reaction cross sections for 24 p-shell isotopes, including ^{8,9}Li, ^{10−12}Be, ^{10,13−15}B, ^{12,14−19}C, and ^{14,15,17−22}N, measured at relativistic energies (approximately 900A  MeV) on both hydrogen and carbon targets. For the first time, we reveal a universal rapid increase in the charge pickup cross sections of unstable projectiles with isospin asymmetry along several isotopic chains. The cross sections can be decoupled into distinct contributions from the mass number and isospin asymmetry of the projectile, highlighting the critical role of the latter, and can be formulated empirically.